Finding Equation of a Line Given the Slope and a Point on It
Date: 08/24/2006 at 19:26:45 From: Sara Subject: getting the equation of a line from y=mx+b to ax+by+c=0 I'm trying to figure out how to convert a line from slope-intercept form to general form, ax + by + c = 0. I'm given one set of points and the slope: (2,-1) and m = 1/4. I don't know where to start. Thanks!
Date: 08/24/2006 at 21:24:26 From: Doctor Rick Subject: Re: getting the equation of a line from y=mx+b to ax+by+c=0 Hi, Sara. Let's work through a different problem so that you can do yours on your own. I'll do (-4,2) m = 3 First of all, many of us would start with the point-slope form, not the slope-intercept form, because we know a point and the slope, not the slope and the y-intercept. The point-slope form is y = m(x-a) + b where the slope is m and the point is (a,b). Plugging in the numbers, I get y = 3(x - -4) + 2 I simplify this equation; simplification pretty much leads me to the slope-intercept form, because that's the simplest form. y = 3(x + 4) + 2 y = 3x + 3*4 + 2 y = 3x + 14 If you don't want to remember one more formula, you can certainly use the slope-intercept form, but it takes more than just plugging in numbers. I start by plugging in the slope, which I know: y = mx + b y = 3x + b To find b, I use the fact that (-4,2) is a solution to the equation. I replace x by -4 and y by 2: 2 = 3*(-4) + b Then I solve this equation for b: 2 = -12 + b 2 + 12 = b 14 = b Going back to the incomplete slope-intercept form, I can now replace b by 14: y = 3x + b y = 3x + 14 That's the same answer I got the first way. It's your choice: whether you want to have to remember more (the point-slope form) or do more work (solving for b). Now we've got the equation in simplest (slope-intercept) form. We want to put the equation y = 3x + 14 into the form ax + by + c = 0 This is a bit odd because it means making the equation *less* simple. Let's start by making one side zero, since we know we want that. I'll make the left side zero (because it has less on it to start with), then switch sides: 0 = 3x + 14 - y 3x + 14 - y = 0 Now let's rearrange the terms to the correct order (term containing x, term containing y, constant term): 3x - y + 14 = 0 To me, that's all we need to do. If it doesn't look like the exact form to you, remember that subtracting a number is the same as adding the opposite of it: 3x + -y + 14 = 0 and that the opposite of a number can be obtained by multiplying it by -1: 3x + -1y + 14 = 0 Now we can see explicitly that a = 3, b = -1, and c = 14. For the sake of neatness and uniformity (and to help the teacher by having everyone write the answer in exactly the same form), we like to make all the coefficients (a, b, and c) integers if possible-- it isn't always possible--and to make "a" positive. If I had gotten to -x + (1/3)y - 14/3 = 0 I would want to multiply through by the denominator, 3: 3(-x + (1/3)y - 14/3) = 3*0 3(-x) + 3(1/3)y - 3(14/3) = 0 -3x + y - 14 = 0 Then I'd multiply by -1 to make the coefficient of x positive: -1(-3x + y - 14) = -1*0 3x - y + 14 = 0 I'd like to see you do your problem following the same method (or rather, one of these methods) to see if you've got the idea. If you're still confused about something, feel free to ask me about it. - Doctor Rick, The Math Forum http://mathforum.org/dr.math/
Search the Dr. Math Library:
Ask Dr. MathTM
© 1994- The Math Forum at NCTM. All rights reserved.